1996
DOI: 10.1007/s002040050352
|View full text |Cite
|
Sign up to set email alerts
|

Long-term cadmium exposure induces anemia in rats through hypoinduction of erythropoietin in the kidneys

Abstract: Cadmium (Cd), a highly toxic heavy metal, is distributed widely in the general environment of today. The characteristic clinical manifestations of chronic Cd intoxication include renal proximal tubular dysfunction, general osteomalacia with severe pains, and anemia. We have recently reported that the serum level of erythropoietin (EPO) remained low despite the severe anemia in patients with Itai-itai disease, the most severe form of chronic Cd intoxication. In order to prove that the anemia observed in chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
48
5

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 17 publications
18
48
5
Order By: Relevance
“…The inhibitory effect of Cd on the digestive and absorption enzymes may also account for the decreased feed efficiency observed in the Cd treated rats. The increased accumulation of Cd observed in the liver and kidney of Cd exposed rats is in consonance with earlier reports [16,21,22]. Examination of the cadmium levels in the liver of rats after both periods of exposure to cadmium shows that it was consistently higher than the level in kidney.…”
Section: Cadmium Exposure Alters Oxidative Enzymes O R I G I N a L P supporting
confidence: 92%
See 3 more Smart Citations
“…The inhibitory effect of Cd on the digestive and absorption enzymes may also account for the decreased feed efficiency observed in the Cd treated rats. The increased accumulation of Cd observed in the liver and kidney of Cd exposed rats is in consonance with earlier reports [16,21,22]. Examination of the cadmium levels in the liver of rats after both periods of exposure to cadmium shows that it was consistently higher than the level in kidney.…”
Section: Cadmium Exposure Alters Oxidative Enzymes O R I G I N a L P supporting
confidence: 92%
“…The decrease in weight gain of the rats is in consonance with previous reports on the effect of cadmium on weight gain of rats [16,17]. The decrease in weight gain and the corresponding increase in dry fecal output of the Cd trea ted rats is also consistent with previous reports on the inhibitory effect of Cd on digestive and absorption enzymes in rats [18][19][20].…”
Section: Cadmium Exposure Alters Oxidative Enzymes O R I G I N a L P supporting
confidence: 91%
See 2 more Smart Citations
“…Several Fe(II)-dependent enzymes, such as the HIF-prolyl hydroxylase (PHD 1-3) and asparagine hydroxylase (FIH-1), regulate HIF-1α stability and activation. Numerous studies have shown that HIF-1α is not only regulated by oxygen tension, but also by various other stimuli, such as transition metals, which can mimic hypoxia to stabilize HIF-1α protein in cultured cells (Horiguchi et al, 1996;Oshiro et al, 1998;Chun et al, 2000;Hossain et al, 2000;Gao et al, 2002bGao et al, , 2004Yuan et al, 2003;Hwang et al, 2004;van Heerden et al, 2004;Zhao et al, 2004). Since Fe(II) is an important cofactor for these hydroxylases and loosely bound to two histidine sites in these enzymes, non-iron metal ions may decrease the activity of these enzymes by either decreasing cellular iron level or directly replacing iron in the enzymes that hydroxylate HIF.…”
Section: Discussionmentioning
confidence: 99%